Database management inventory system - Aripin, Syahida (2006)
Inventory control systems in construction industry needs systematic database management system. Inventory involved in construction industry are materials, machineries, spare parts, etc. This study is about to develop the inventory system that can be applied in construction industry. The objectives are to identify the problems involved in the implementation of the current inventory system at the spare parts store, Logistics and Machineries Department (LMD), PROPEL Berhad, to identify the needs of systematic inventory system at the spare parts store and to develop the prototype of the inventory system that can be implemented at the spare parts store. A case study has been carried out at LMD, PROPEL Berhad for the prototype development. The prototype used Microsoft Access and Bar Coding System. The prototype not only benefit to the person who in-charged with the system, but also benefit to all staffs dealing with the spare parts store by making it faster, more accurate and easier.